Implementation Of The Corporate Social Responsibility (CSR) Program In Improving Community Welfare In Lubuk Pinang Village Mukomuko District : Implementasi Program Corporate Social Responsibility (CSR) Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Lubuk Pinang Kabupaten Mukomuko - Liffia Riska Pinda; M. Fachri Adnan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research was motivated by a problem discovered by the Corporate Social Responsibility (CSR) of PT. Sapta Sentosa Jaya Abadi, Lubuk Pinang Village, there were still several inequalities that occurred which were not in accordance with community expectations. This research aims to analyze the implementation of Corporate Social Responsibility (CSR) carried out by PT. Sapta Sentosa Jaya Abadi to pay attention to environmental conditions and community welfare and to find out what factors influence them. This research is included in the field research category with a qualitative approach. Data collection techniques use interviews and documentation. The research results show that PT. Sapta Sentosa Jaya Abadi has indeed implemented Corporate Social Responsibility (CSR), in this case the company has carried out various kinds of social activities towards the environment and society, but there are still several shortcomings and obstacles in the process. Apart from that, there are factors that influence the implementation of PT Sapta Sentosa Jaya Abadi's Corporate Social Responsibility (CSR) program, seen from supporting and inhibiting factors. The supporting factor is the synchronization between the proposals from the buffer villages and the CSR program which works together to implement the CSR program of PT. Sapta Sentosa Jaya Abadi in improving the welfare of the community in Lubuk Pinang village. Meanwhile, the inhibiting factor that is an obstacle is that CSR which is realized is not yet significant for society.